2000
DOI: 10.1007/pl00002332
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Radiation Effects of Gadolinium and Boron Neutron Capture Reactions

Abstract: When an equal number of atoms were present, Gd-157 was effective as B-10 when exposed to an equal number of thermal neutrons. However, there was no benefit observed in the combination of Gd-157 and B-10 for neutron capture therapy. Further studies are needed to determine optimal Gd-157 and B-10 concentrations as a function of tumor dimension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In this study, Gd(III) accumulated at 162 ppm intracellularly, calculated on the basis of the 153 Gd radioactivity, in SHIN3 tumors in vivo at 1 day after injection, and 93% of Gd(III) was located in the SHIN3 cells. In a recent study, 400-800 ppm of extracellular Gd(III)-DTPA as well as 30-51 ppm of 10 B was reported as effective to kill cancer cells with neutron beam irradiation (30). Therefore, the concentration of Gd(III) with Av-G6Gd in SHIN3 cells should be adequate for Gd-NCT.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, Gd(III) accumulated at 162 ppm intracellularly, calculated on the basis of the 153 Gd radioactivity, in SHIN3 tumors in vivo at 1 day after injection, and 93% of Gd(III) was located in the SHIN3 cells. In a recent study, 400-800 ppm of extracellular Gd(III)-DTPA as well as 30-51 ppm of 10 B was reported as effective to kill cancer cells with neutron beam irradiation (30). Therefore, the concentration of Gd(III) with Av-G6Gd in SHIN3 cells should be adequate for Gd-NCT.…”
Section: Discussionmentioning
confidence: 99%
“…In general, these studies have indicated that folatecoated Gd nanoparticles may have potential of selectively delivering high concentrations of Gd to tumors thereby enhancing the success of NCT. Previous reports have suggested that targeted Gd-NCT strategies may be of therapeutic interest (Akine et al, 1990;Tokuuye et al, 2000). Folate-coated nanoparticles may therefore serve as effective carrier systems for Gd-NCT since (i) nanoparticle size of ∼100 nm could facilitate internalization by tumor cells, (ii) the formulations contain high concentrations of Gd, (iii) nanoparticles may potentially enhance the therapeutic potential Gd-NCT via selective uptake by folate receptors, and (iv) previous studies have shown that presence of Gd in the intracellular space can enhance the therapeutic effectiveness of Gd-NCT (Akine et al, 1990).…”
Section: Synthesis Of Gadolinium Hexanedione (Gdh)mentioning
confidence: 99%
“…The potential for NCT utilizing capture agents other than boron-10 has been studied previously (Tokuyye et al 2000, Miller et al 1993, Masiaskowski et al 1992, Watanabe et al 2002, Allen et al 1989, Maeda et al 1995, Kagehira et al 1994. The neutron interaction characteristics are generally similar between 10 B and 157 Gd, as shown by the total cross sections plotted together in figure 1.…”
Section: Introductionmentioning
confidence: 99%